Effects of Topiramate Drug on Biological, Hormonal and Histological Parameters in Pregnant Albino Rats and Embryos - Amel A. Altaee (Journal of Global Pharma Technology, 2017)
The present study aimed to elucidate the effect of Topiramate drug (100 mg/kg b.wt) on some parameter in pregnant albino rats including serum reproductive hormones level , Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH) and Estradiol (E2)), body weight gain, uterus weight, on the implantation and desorption of embryo, diameter of follicle in ovary and development of neural tube of embryos in pregnant albino rats for different periods (7,9,12,14 and 21 days) of gestation . The hormonal results showed no significant change (P ≤ 0.05) in the mean levels of LH and FSH hormone for treated groups when compared with control groups for days 7, 9, 12, 14 and 21 of pregnancy, but there was a significant increase (P ≤ 0.05) in the mean levels of E2 hormone for treated groups as compared with control groups. There is significant increase in the numbers of desorption embryos in treated groups for days 7, 9, 12, 14 and 21of pregnancy, as compared with control groups. While the study showed significant decrease in the number of implantation sites in treated groups as compared with control groups. The results of this study revealed no significant increase in the secondary follicle diameters in treated groups of 9 and 12 days and tertiary follicle of 7 days of pregnancy, as compared with control. The diameters of epithelial and marginal layers of neuro-ectoderm in days 9 of pregnancy for treated groups showed significant increase as compared with control groups.Keywords: Topiramate, Rats, Embryo, Neural tube, Ovary.